Pengaruh Kinerja Lingkungan, Leverage, Ukuran Perusahaan, Dan Profitabilitas Terhadap Pengungkapan Lingkungan Pada Perusahaan BUMN - Aldi Haslanu; Rindu Rika Gamayuni; Ade Widiyanti (Syntax Idea, 2022)
Environmental Disclosure is a form of corporate social responsibility that includes regulations, policies, environmental effects, and applicable legal aspects. This study aims to determine the effect of environmental performance, leverage, firm size, and profitability on environmental disclosure in state-owned companies listed on the Indonesia Stock Exchange (IDX) during 2016-2020. The research method used in this study is a descriptive method with a quantitative approach. While the data used in this study is secondary data obtained from the IDX website (www.idx.com) and the websites of each company. This research uses multiple linear regression analysis model. This study obtained results that prove that environmental performance and firm size have a significant positive effect on environmental disclosure; leverage has a significant negative effect on environmental disclosure; profitability has no effect on environmental disclosure. The coefficient of determination analysis shows that the adjusted value of R squared in the coefficient of determination test is 31.6%, where the remaining 68.4% is influenced by other variables. This shows that the independent variable in this study does not have enough effect on the dependent variable because there are other variables that have a major influence on environmental disclosure.